Pemakaian Skincare pada Perempuan Masa Iddah dalam Perspektif Kitab Tausyikh Karya Syekh Nawawi: (Perspektif Kitab Tausyikh Karya Syekh Nawawi) - Ulum, Bahrul; Rahmawati, Isma (JURNAL PUSAKA, 2024)
Nowadays, skincare is very widely used by women, using skincare has become a woman's primary need. Actually, there are no prohibitions on using skincare, as long as the items used are BPOM certified and verified as halal so that they remain safe when used. However, if it is related to iddah, are women still allowed to use skincare during the iddah period?, then it is still necessary to study the law from the perspective of the Shafi'i Madzhab, especially in the Tausyikh Book written by Muhammad Nawawi bin Umar Al-Jawi. The aim of this research is to find out what the law is for using skincare for women during the Iddah period, because women still have very little understanding about this. In this research, the method used is library research by collecting individual words or sentences that are considered relevant in discussing a woman's iddah, especially in the Imam Syafi'i Madzhab. Primary data sources are Syafi'iyah books, while secondary data are books and journals. From this research, it was found that the majority of Syafi'iyah ulama' did not allow the use of skincare on women who were on iddah to die and allowed it on women who were on iddah for divorce because this was related to ihdad, those who were required to perform ihdad were women who were on iddah to die and not on iddah on divorce. Because the wisdom of berihdad is nothing other than a form of condolence for the death of her husband. Keywords: skincare; woman; iddah; Tausyikh; divorce law